EFFECT OF DAILY TRIP SYSTEM ON PT. X CONTRACTOR WORKER FATIGUE AT OFFSHORE SITE - Nuraini, Desi; Ramdhan, Doni Hikmat (Journal of Vocational Health Studies, 2021)
Background: PT. X implements a daily trip method that takes ±1,5 hours to arrive at the offshore platforms. Travel time that's too long can cause fatigue. Purpose: Analyzing the effect of a daily trip system on PT. X contractor worker fatigue at offshore site. Method: This research was conducted at one of PT. X's offshore Gresik Sites in June 2021 used Fatigue Assessment Scale (FAS) questionnaire with observational analytics method and cross-sectional study design. Research samples were taken from the population of 153 construction workers PT. X at offshore site. The data obtained were analyzed using quantitative approach, data analysis used univariate analysis and bivariate analysis, chi-square statistical test with significance value or confidence interval was 95% and error interval was 5%  (CI = 95% and α = 0.05). Result: PT. X Contractor workers at the offshore site had 85 workers (55.56%) that get fatigue. Statistical analysis test showed there was no significant relationship between a daily trip system with fatigue on PT. X Contractor workers at the offshore site (p-value = 0.140). Factors that affect fatigue on PT. X Contractor workers at the offshore site were age, body mass index, and workload (p-value successive were 0.047, 0.014, and 0.001). Conclusion: A daily trip system has no effect with fatigue on PT. X contractor worker at the offshore site, recommended for the contractor to improve the BMI and manage the workload so that its more evenly distributed.